2019
DOI: 10.1038/s41598-019-45844-2
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Zn2+ transients modulate global gene expression in dissociated rat hippocampal neurons

Abstract: Zinc (Zn 2+ ) is an integral component of many proteins and has been shown to act in a regulatory capacity in different mammalian systems, including as a neurotransmitter in neurons throughout the brain. While Zn 2+ plays an important role in modulating neuronal potentiation and synaptic plasticity, little is known about the signaling mechanisms of this regulation. In dissociated rat hippocampal neuron cultures, we used fluorescent Zn 2+ sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 75 publications
(82 reference statements)
2
49
0
Order By: Relevance
“…Approximately 90% of the zinc present in the brain is protein-bound, contributing to the function of over 2000 proteins [ 3 , 4 ]. Indeed, zinc acts as a cofactor for over 300 enzymes, and, in the hippocampus alone, changes in cytosolic zinc can modulate the expression of over 900 genes [ 5 , 6 ], many of which are linked to the cell cycle, neurite extension, and synaptic growth [ 6 , 7 , 8 , 9 ]. Most of the remaining labile, nominally unbound or weakly bound zinc in the brain is present in synaptic vesicles of a large population of excitatory glutamatergic neurons throughout the cerebral cortex, hippocampus, striatum, and auditory brainstem [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 90% of the zinc present in the brain is protein-bound, contributing to the function of over 2000 proteins [ 3 , 4 ]. Indeed, zinc acts as a cofactor for over 300 enzymes, and, in the hippocampus alone, changes in cytosolic zinc can modulate the expression of over 900 genes [ 5 , 6 ], many of which are linked to the cell cycle, neurite extension, and synaptic growth [ 6 , 7 , 8 , 9 ]. Most of the remaining labile, nominally unbound or weakly bound zinc in the brain is present in synaptic vesicles of a large population of excitatory glutamatergic neurons throughout the cerebral cortex, hippocampus, striatum, and auditory brainstem [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…While the observed stimulation-dependent rise in intracellular Zn 2+ could be related to the potential release of a synaptic Zn 2+ pool in these neuron cultures, we were previously unable to visualize synaptic Zn 2+ in dissociated culture 23 . Based on this and other previous work 22 , we suspected that synaptically released Zn 2+ was not the primary source of the observed intracellular Zn 2+ signal.…”
Section: Resultsmentioning
confidence: 89%
“…In dissociated hippocampal neuron culture, stimulation with glutamate/glycine 22 or KCl 23 has been shown to increase intracellular Zn 2+ , and this Zn 2+ signal has important downstream signaling consequences. This Zn 2+ has been suggested to arise from an intracellular source in a Ca 2+ -dependent manner, and previous studies have indicated that during glutamate stimulation the Zn 2+ signal may be downstream of Ca 2+ -induced neuronal acidification 22,24 .…”
mentioning
confidence: 99%
“…Data were corrected for uptake in the presence of FCCP and normalized to the TPEN condition. Glutamate uptake into vesicles was dose-dependently facilitated by Zn 2+ and exhibited a ∼2 fold increase in the maximal uptake with an EC50 of ∼25 nM (Figure 6B and C), a physiologically relevant cytoplasmic [Zn 2+ ] in view of the confined volume of a typical presynaptic compartment (3.7 x 10 -22 L, (Goch and Bal, 2020; Wilhelm et al, 2014)) and activity-dependent increase of cytoplasmic [Zn 2+ ] (Sanford et al, 2019). To determine if the facilitatory Zn 2+ effect on VGLUT1 activity is mediated by ZnT3, we performed the glutamate uptake assay in preparations from ZnT3 knockout (KO) mice.…”
Section: Resultsmentioning
confidence: 99%